Answer:
3
Step-by-step explanation:
how much would a 2 ton truck weigh on the moon? divide by 6 because 2x3=6 and the moon has low gravity so its is diffrent from earths gravity
Answer:
no
Step-by-step explanation:
A proportional relationship must go through (0,0)
c=7n+2
0 = 7(0) +2
0 = 2
This is not true so it is not a proportional relationship
Answer:
- (0, 4)
- (-1, 16/ 3)
- (-9/ 2, 10)
Step-by-step explanation:
In an ordered pair the term before the comma is the x variable and the term after the comma is the y variable.
1.
4x + 3y = 12 . . . . . .(0, _)
here were given the x variable
finding the other term
4× 0 + 3y = 12
3y = 12
y = 4
therefore the ordered pair is <u>(0, 4) </u>
2.
. . . . . . . (-1, _)
here were given the x variable
4 × -1 + 3y = 12
3y = 12 + 4
3y = 16
y = 16/ 3
ordered pair is <u>(-1, 16/ 3)</u>
3.
. . . . . . . . (_, 10)
here were given the y variable
finding the other term
4x + 3 × 10 = 12
4x + 30 = 12
4x = 12 - 30
4x = -18
dividing both sides by 2
2x = -9
x = -9/ 2
ordered pair is<u> (-9/ 2, 10)</u>
Answer:
x= -4
Step-by-step explanation:
Simplifying
5x + -4 = 7x + 4
Solving
-4 + 5x = 4 + 7x
Move all terms containing x to the left, all other terms to the right.
Add '-7x' to each side of the equation.
-4 + 5x + -7x = 4 + 7x + -7x
Combine like terms: 5x + -7x = -2x
-4 + -2x = 4 + 7x + -7x
Combine like terms: 7x + -7x = 0
-4 + -2x = 4 + 0
-4 + -2x = 4
Add '4' to each side of the equation.
-4 + 4 + -2x = 4 + 4
Combine like terms: -4 + 4 = 0
0 + -2x = 4 + 4
-2x = 4 + 4
Combine like terms: 4 + 4 = 8
-2x = 8
Divide each side by '-2'.
x = -4
Simplifying
x = -4